2011
DOI: 10.1002/dvdy.22544
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenin3 initiates stepwise delamination of differentiating endocrine cells during pancreas development

Abstract: During development, pancreatic endocrine cells are specified within the pancreatic epithelium. They subsequently delaminate out of the epithelium and cluster in the mesenchyme to form the islets of Langerhans. Neurogenin3 (Ngn3) is a transcription factor required for the differentiation of all endocrine cells and we investigated its role in their delamination. We observed in the mouse pancreas that most Ngn3-positive cells have lost contact with the lumen of the epithelium, showing that the delamination from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 60 publications
13
124
0
1
Order By: Relevance
“…In addition, KRT20 expression has been found to be downregulated in the in vitro human ductal-to-b-cell differentiation process (Dodge et al 2009, Téllez et al 2013, supporting differential KRT20 expression in ductal cells depending on the maturation status. On the other hand, the reduced cytoplasmic accumulation of b-catenin in newly formed regenerative ducts could facilitate delamination of endocrine precursors from ductal structures as found in embryonic pancreas development (Kesavan et al 2009, Gouzi et al 2011. It has been recently reported that loss of E-cadherin accumulation in the plasma membrane by sustained expression of Neurog3 in the mouse endoderm is sufficient to trigger cell delamination from the endodermal epithelium (Gouzi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KRT20 expression has been found to be downregulated in the in vitro human ductal-to-b-cell differentiation process (Dodge et al 2009, Téllez et al 2013, supporting differential KRT20 expression in ductal cells depending on the maturation status. On the other hand, the reduced cytoplasmic accumulation of b-catenin in newly formed regenerative ducts could facilitate delamination of endocrine precursors from ductal structures as found in embryonic pancreas development (Kesavan et al 2009, Gouzi et al 2011. It has been recently reported that loss of E-cadherin accumulation in the plasma membrane by sustained expression of Neurog3 in the mouse endoderm is sufficient to trigger cell delamination from the endodermal epithelium (Gouzi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…+ endocrine progenitors delaminate from the ducts and migrate to form endocrine cells [9,10]. By late gestation (around E18.5), the endocrine cells are loosely arranged as small clusters; at this stage bcells cannot sense glucose and secrete insulin [11,12].…”
Section: Onward Ngn3mentioning
confidence: 99%
“…The restriction towards a terminally differentiated endocrine cell occurs progressively [10]. Endocrine differentiation requires inhibition of NOTCH signalling and transient activation of neurogenin 3 (NEUROG3) in epithelial trunk progenitor cells, and is accompanied by exit from the cell cycle and migration into the mesenchyme [11][12][13][14][15][16][17][18]. Downstream, regulators of beta cell specification include: paired box 4 (PAX4), neurogenic differentiation 1 (NEUROD1), regulatory factor X, 6 (RFX6), NK2 homeobox 2 (NKX2.2), NK6 homeobox 1 (NKX6.1) and v-maf avian musculoaponeurotic fibrosarcoma oncogene homologue A (MAFA), among others [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%